New concept of 3D bio-inspired solar thermal collector. (1st January 2020) - Fraisse, Gilles; Merlin, Gérard; Pailha, Mickael; Cloet, David; Bernard, Lucas
Highlights: The concept of a new 3D bio-inspired solar thermal collector has been validated. The performances of the STT can be evaluated using dimensionless equations. The optimal solutions are similar in the cases with 3, 4 and 5 branches per node. Optimal solutions are not obtained with the Hess-Murray law. The entropy criterion maximizes the thermal efficiency (air flow with low ΔP). Abstract: The aim of the present work was to develop a new type of solar thermal collector tree shape in three dimensions. It is a Solar Thermal Tree (STT) whose branches and trunk consist of tubular absorbers glazed or not. The article presents the validation of the concept with a medium-scale prototype. The numerical modeling of the STT is first described, then the comparison of the experimental and numerical results, the evaluation of the performances based on dimensionless equations, and finally the multi-criteria optimization. The model has been used to identify the dimensionless equations (thermal efficiency and pressure drop) from a small number of parameters. These equations can be used to design the STT for different applications. It also enabled to define optimal solutions (Pareto) by considering the two performance functions in a configuration close to that of the prototype. Optimal solutions are compared with the experiment using the prototype, a solution that minimizes the creation of entropy generated by flow and heat transfer, and a solution based on the Hess-Murray law that minimizes flow resistance in laminar or turbulent flow. The optimization criterion based on entropy generation is the most relevant because the entropy generated by the air flow is very low compared to heat transfer. Also, optimization leads to maximizing thermal efficiency. Finally, the design of a 4 m 2 STT that can be used to preheat the building's fresh air (0 °C) has been optimized. This new configuration, based on vacuum tubes has a thermal efficiency of 58%.